Race classification using deep learning - Khan, Khalil; Khan, Rehan Ullah; Ali, Jehad; Uddin, Irfan; Khan, Sahib; Roh, Byeong Hee (Computers, Materials and Continua, 2021)
Race classification is a long-standing challenge in the field of face image analysis. The investigation of salient facial features is an important task to avoid processing all face parts. Face segmentation strongly benefits several face analysis tasks, including ethnicity and race classification. We propose a race-classification algorithm using a prior face segmentation framework. A deep convolutional neural network (DCNN) was used to construct a face segmentation model. For training the DCNN, we label face images according to seven different classes, that is, nose, skin, hair, eyes, brows, back, andmouth. The DCNN model developed in the first phase was used to create segmentation results. The probabilistic classification method is used, and probability maps (PMs) are created for each semantic class. We investigated five salient facial features from among seven that help in race classification. Features are extracted from the PMs of five classes, and a new model is trained based on the DCNN. We assessed the performance of the proposed race classification method on four standard face datasets, reporting superior results compared with previous studies.
Keywords: Different class; Face image analysis; Face segmentation; Probabilistic classification method; Probability maps; Race classification; Salient facial features; Segmentation results; Deep learning; Face analysis; Facial feature; Learning race; Race classification